The effect and mechanism of Fushen Granule on gut microbiome in the prevention and treatment of chronic renal failure - Wang, Lin; Xu, Ao; Wang, Jinxiang; Fan, Guorong; Liu, Ruiqi; Wei, Lijuan; Pei, Ming (Frontiers in Cellular and Infection Microbiology, 2024)
Background Fushen Granule is an improved granule based on the classic formula Fushen Formula, which is used for the treatment of peritoneal dialysis-related intestinal dysfunction in patients with end-stage renal disease. However, the effect and mechanism of this granule on the prevention and treatment of chronic renal failure have not been fully elucidated. Methods A 5/6 nephrectomy model of CRF was induced and Fushen Granule was administered at low and high doses to observe its effects on renal function, D-lactate, serum endotoxin, and intestinal-derived metabolic toxins. The 16SrRNA sequencing method was used to analyze the abundance and structure of the intestinal flora of CRF rats. A FMT assay was also used to evaluate the effects of transplantation of Fushen Granule fecal bacteria on renal-related functional parameters and metabolic toxins in CRF rats. Results Gavage administration of Fushen Granule at low and high doses down-regulated creatinine, urea nitrogen, 24-h urine microalbumin, D-lactate, endotoxin, and the intestinal-derived toxins indophenol sulphateand p-cresol sulphate in CRF rats. Compared with the sham-operated group in the same period, CRF rats had a decreased abundance of the firmicutes phylum and an increased abundance of the bacteroidetes phylum at the phylum level, and a decreasing trend of the lactobacillus genus at the genus level. Fushen Granule intervention increased the abundance of the firmicutes phylum, decreased the abundance of the bacteroidetes phylum, and increased the abundance of the lactobacillus genus. The transplantation of Fushen Granule fecal bacteria significantly reduced creatinine(Cr), blood urea nitrogen(Bun), uric acid(UA), 24-h urinary microalbumin, D-lactate, serum endotoxin, and enterogenic metabolic toxins in CRF rats. Compared with the sham-operated group, the transplantation of Fushen Granule fecal bacteria modulated the Firmicutes and Bacteroidetes phyla and the Lactobacillus genus. Conclusion Fushen Granule improved renal function and intestinal barrier function by regulating intestinal flora, inhibiting renal fibrosis, and delaying the progression of chronic renal failure.